USE OF ARTIFICIAL INTELLIGENCE METHODS IN OPERATIONAL PLANNING OF TEXTILE PRODUCTION - Yuldoshev, Nuritdin; Tursunov, Bobir; Qozoqov, Saidmuhtor (Journal of process management and new technologies, 2018)
In this article, the authors analyzed the widely used methods of artificial intelligence in world practice, described the production management system. Also, the main functions are considered and it is determined that the organization of any production begins with its operational planning. And in the basis of production planning functions are various methods and algorithms of artificial intelligence. The authors considered important stages in the construction of the neural network system in planning, and discussed the most common methods and algorithms of artificial intelligence for planning textile production: taboo search method, ant algorithm, genetic algorithms, neural networks.